The frequency of metabolic syndrome in psychiatric patients using antidepressant medications - Findikli, Ebru; Izci, Filiz; Camkurt, Mehmet Akif; Cetinkaya, Ali; Findikli, Huseyin Avni; Atmaca, Murad (Cumhuriyet Univ Tip Fak Psikiyatri Anabilim Dali, 2017)
Objective: There are limited studies investigating the metabolic syndrome (MS) in patients using antidepressants. This study examines and compares the prevalence of MS and related factors in psychiatric patients taking various antidepressants at an outpatient clinic. Methods: The study comprised a total of 70 patients using fluoxetine, paroxetine, sertralin, citalopram, essitalopram, clomipramine and venlafaxine aged 18-60 years with depressive and anxiety disorder. MS rates of patients (according to National Cholesterol Education Program-Adult Treatment Panel III-(NCEP III)) who met the study criteria were obtained. Results: In our study metabolic syndrome frequency was 32.8% in total patient groups according to NCEP-III criteria. The higher metabolic syndrome frequency was found in drug groups such as clomipramine, paroxetine and venlafaxine groups. The safest drug for metabolic syndrome was fluoxetine as seen in its relevant group. Conclusion: Conventional antidepressants may cause metabolic syndrome which is important for mortality, morbidity and quality of life of psychiatric patients.
Antidepresan kullanan psikiyatrik hastalarda metabolik sendrom sıklığı
Keywords: metabolic syndrome; venlafaxine; clomipramine; fluoxetine; depressive disorder; anxiety disorder